Edukasi Kesehatan Tentang Penyakit Diabetes Melitus Di Rt.11 Puskesmas Jembatan Kecil Kota Bengkulu - Riska Riska; Ismiarty Oktariany; Khairini Aulia; Yuliana Yuliana; Andari Anisa; Helvita Sari; Mariza Afrianti; Rafika Ramlis; Desi Aulia Umami (Jurnal Pakar Pengabdian Kesehatan, 2025)
According to WHO, Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose (or blood sugar) levels. Number of Sufferers: An estimated 589 million to 830 million adults (aged 20–79 years) are living with diabetes worldwide in 2024, 2050 Prediction: This figure is projected to jump to 853 million people. Based on World Ranking Statistics: Indonesia ranks 5th in the world with the highest number of diabetes sufferers. Number of Sufferers: Reaching around 20.4 million people in 2024. National Prevalence: Around 11.3% of the total adult population of Indonesia, a figure higher than the average for the Southeast Asia region (10.8%). The cause of diabetes is a combination of genetic and lifestyle factors, such as lack of exercise, unhealthy diet (high in sugar and fat), obesity, and stress, which cause the body to be unable to produce or use insulin effectively, so that sugar accumulates in the blood. This outreach program aims to help reduce diabetes rates and increase awareness of diabetes among all groups at the Integrated Health Post (Posyandu) RT. 11, Jembatan Kecil Village, Singaran Pati District, Bengkulu City. The outreach program utilizes diabetes education. It is hoped that this will increase public awareness of diabetes and prevent the number of cases from increasing.